Protecting Socioeconomically Vulnerable Defendants: Poverty Criminalization in Indonesia and Saudi Arabia - Abriantinus Abriantinus; Vieta Imelda Cornelis; Syahrul Borman; Nur Handayati; Khalid Saleh Y. Alammari (RechtIdee, 2026)
Study Objectives: This article examines how Indonesian and Saudi Arabian criminal justice frameworks protect, or fail to protect, defendants whose socio-economic vulnerability shapes their exposure to the criminal process and punishment.Method/Approach: It uses normative legal research, including statute, conceptual, and functional comparative approaches.Novelty: This study advances a social vulnerability-sensitive criminal justice model of poverty.Findings: The study finds a shared formal commitment to defense rights but divergent institutional designs. Indonesia now combines a statutory legal-aid scheme with the 2025 Criminal Procedure Code, which requires officials to inform indigent persons of legal-aid rights and appoint counsel in specified cases. The 2023 Criminal Code also provides a stronger foundation for individualized and non-custodial sentencing. Saudi Arabia recognizes the accused’s right to counsel during investigation and trial and provides a state-funded appointment route in serious crimes, but that route depends on a request, judicial verification of indigence, and a serious-crime threshold. Neither system expressly requires a court to assess the poverty-related consequences of prosecution, fines, detention, or imprisonment.Conclusion: Defense rights require meaningful access to defense, an ability-to-pay review, a custody-necessity test, written reasons that address social impact, and, where proportionate, restorative or community-based responses.